Analysing the Detection of Rheumatoid Arthritis using Image Processing Techniques - Pari, Sheba (International Journal of Computer Sciences and Engineering, 2025)
A huge volume of research have been made in the medical field for finding out inflammatory disorder which is rheumatoid arthritis which is one form of arthritis which affects joints. Identifying the onset of the disease should be done as early as possible to start the proper treatment, to prevent maximum deformity and for better quality of living. Radiography helps in detecting rheumatoid arthritis but there is reduced accuracy and is slower in detecting as it starts detecting after deformity(irreversible process) of joints have started. Magnetic resonance imaging may be more precise and accurate in identifying deformities. In Magnetic resonance imaging, images are analyzed through different image processing techniques. This paper is primarily aimed at stating the advantages of Magnetic resonance imaging over other techniques and after Magnetic resonance imaging scan has been done, making use of image processing techniques to obtain the final image for detection of the disorder.